1997
DOI: 10.1038/sj.bmt.1700888
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with acute myelogenous leukemia in prolonged first complete remission after bone marrow transplantation (allogeneic or autologous) or chemotherapy: a cross-sectional study of the EORTC-GIMEMA AML 8A trial

Abstract: Summary:vary from one study to another, they show generally a lower risk of relapse, and a longer disease-free survival (DFS) after AlloBMT and ABMT than after ICC. A cross-sectional study of quality of life (QOL) was performed in 98 patients in continued first complete From 1986 to 1992, the EORTC and GIMEMA Leukemia Cooperative Groups prospectively compared these remission (CR) for 1-7.4 years, after inclusion in the AML 8A trial which prospectively compared allogeneic three therapeutic options: patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
3
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 5 publications
6
89
3
3
Order By: Relevance
“…However, these results were conflicting, and few have controlled confounding backgrounds. [21][22][23][24][25][26][27] In a longitudinal study that assessed the QOL in patients treated with allo-HCT, autologous HCT or chemotherapy, the allo-HCT group had higher scores in global QOL, fatigue and sleep disturbance compared with the other two groups. 21 The results may be confounded by the difference in populations between the treatment groups: the allo-HCT group included only leukemia patients and the autologous HCT/chemotherapy groups included only lymphoma patients.…”
Section: Qol Estimates Provided By Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these results were conflicting, and few have controlled confounding backgrounds. [21][22][23][24][25][26][27] In a longitudinal study that assessed the QOL in patients treated with allo-HCT, autologous HCT or chemotherapy, the allo-HCT group had higher scores in global QOL, fatigue and sleep disturbance compared with the other two groups. 21 The results may be confounded by the difference in populations between the treatment groups: the allo-HCT group included only leukemia patients and the autologous HCT/chemotherapy groups included only lymphoma patients.…”
Section: Qol Estimates Provided By Patientsmentioning
confidence: 99%
“…Three studies that included AML in remission reported worse QOL in patients who received Quality of life after treatment for acute leukemia S Kurosawa et al allo-HCT. 24,25,27 Zittoun et al 27 performed a cross-sectional study and showed that physical, role functioning, sexual functioning and overall QOL were significantly lower after allo-HCT than after chemotherapy. In more recent cross-sectional studies with a larger number of AML patients, allo-HCT had an adverse impact on the QOL in many of the dimensions in EORTC QLQ-C30.…”
Section: Qol Estimates Provided By Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been described previously. 22,23 The four questions asked about: (1) sexual interest, (2) activity, (3) pleasure and (4) ability on a three-way scale (increased, unchanged or decreased). One question on the Leukaemia-BMT (QLQ-LEU) module also dealt with pain during sexual intercourse.…”
Section: Qol Assessmentmentioning
confidence: 99%